ChemInform Abstract: Silver‐Catalyzed Functionalization of Esters by Carbene Transfer: The Role of Ylide Zwitterionic Intermediates. Issue 4 (January 2015) - Gava, Riccardo; Fuentes, M. Angeles; Besora, Maria; Belderrain, Tomas R.; Jacob, Kane; Masera, Feliu; Etienne, Michel; Caballero, Ana; Perez, Pedro J.
Abstract A novel carbene transfer reaction from diazoesters to carboxylic acids is developed using a highly fluorinated tris(indazolyl)borate silver complex as catalyst.